PENGENALAN BERETIKA KOMUNIKASI DALAM SOSIAL MEDIA DI KALANGAN REMAJA - Gelgel, N.M.R.A. (Buletin Udayana Mengabdi, 2018)
Technology has important role in people’s life especially in communicating. Nowadays people communicating through new media such as online media and social media. Unfortunately, part of the people access and communicate in social media without ethics. It was risky, because what people said in their social media can entrap by the law. For that reason, it was very important to improve knowledge in how to communicate in social media ethically, especially for teenagers. Teenagers are the most numerous group involved in negative’s social media cases. Activities improving ethics in social media communicating was held in SMAN 1 Gianyar Bali. The activities started with dialogue with highschool student, and shared with them about how we should ethically communicate in social media. Beside dialogue, flyers also given for all the students. From the dialogue, researcher found out that students was not knowing the effects if they didn’t communicate ethically in social media.